Biogeographical patterns of the genus Merodon Meigen, 1803 (Diptera: Syrphidae) in islands of the eastern Mediterranean and adjacent mainland. Issue 3 (12th February 2016) - Vujić, Ante; Petanidou, Theodora; Tscheulin, Thomas; Cardoso, Pedro; Radenković, Snežana; Ståhls, Gunilla; Baturan, Željana; Mijatović, Gorana; Rojo, Santos; Pérez‐Bañón, Celeste; Devalez, Jelle; Andrić, Andrijana; et al.
Abstract: The objective of this study was to obtain a biogeographical perspective on the hoverfly genus Merodon (Diptera, Syrphidae) based on data from 32 islands in the Aegean and Ionian archipelagoes vis‐à‐vis the adjacent mainland. In this part of the world, the genus comprises 57 species, out of more than 160 species described worldwide. The importance of eco‐geographical variables (area, elevation, distance to the nearest island and distance to the nearest mainland) and the species–area relationship (SAR) were studied in order to explain patterns of species richness. All tests supported the dynamic equilibrium concept. The area and distance to closest island were found to be the most important drivers of species richness on the Aegean and Ionian archipelagoes. Out of three SAR models evaluated in this study, the exponential function fitted our data best. It was found that a power model with no intercept value ( C = 1) performed even better by using symbolic regression for non‐linear equation optimisation. The cluster and null‐model analyses performed to detect inter‐island similarities and origins of the insular Merodon fauna indicated a clear influence of colonisation history of the species on different islands. The results imply that the current distributions of Merodon species in the study area exhibit the combined effects of historical and present‐day processes.